Influence of the international context on the signing of the Dominican-Spanish recognition treaty in 1855 - Escolano Giménez, Luis Alfonso (UNIV CARLOSIII MADRID, 2021)
The period around the recognition treaty between Spain and the Dominican Republic in 1855 is essential to study the causes of foreign intervention in the Caribbean country,since it reveals both the internal and external dynamics that led to serious instability arising from the struggles among local groups that were supported by different countries with their own goals. Under the pretext of mediating between Haitians and Dominicans,the main powers vied to increase their influence over the Santo Domingo executive,initially by establishing diplomatic relations. Although the first initiatives of the Dominican government to reach an agreement with Spain were rejected by the Madrid cabinet,it eventually decided to establish relations with that of Santo Domingo in order to act on the ground and hinder U.S. expansionism in the Dominican Republic,since the Spanish authorities in Cuba and Puerto Rico considered it a threat to the preservation of these islands. Copyright: © HISPANIA NOVA es una revista debidamente registrada,con ISSN 1138-7319 y Depósito Legal M 9472-1998. Los textos publicados están -si no se indica lo contrario- bajo una licencia Reconocimiento-Sin obras derivadas 3.0 España de Creative Commons. Puede copiarlos,distribuirlos y comunicarlos públicamente siempre que cite su autor y la revista y la institución que los publica y no haga con ellos obras derivadas. La licencia completa se puede consultar en: http://creativecommons.org/licenses/by-nd/3.0/es/deed.es
[INFLUENCIA DEL CONTEXTO INTERNACIONAL SOBRE LA FIRMA DEL TRATADO DE RECONOCIMIENTO DOMINICO-ESPAÑOL EN 1855]